KAJI SIFAT MEKANIK PANEL KARBON KOMPOSIT SANDWICH MENGGUNAKAN METODE VACUUM BAGGING PADA PESAWAT PUNA MALE - Ziansyah, Vendrio; Hestiawan, Hendri; Roseno, Seto (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2024)
The drone is the result of a collaboration to form a consortium between the Agency for the Assessment and Application of Technology (BPPT), the Ministry of Defence, the Indonesian Air Force, ITB, PT Dirgantara Indonesia, and PT LEN Persero. In this research, an analysis of the mechanical properties of the carbon composite sandwich panel was carried out using the vacuum bagging method to determine the compressive strength of the composite material. The data used was taken from the results of compression tests carried out on 5 specimens using the Universal Testing Machine (UTM) TENSILON RTF-2410. From the tests that have been carried out, the average compressive strength data is 1.924 MPa and the strain value is 4.253 %. Compared to the compressive strength of the PUNA MALE aircraft specifications, which is 0.127 MPa and the average pressure value obtained in the compressive test on the carbon sandwich composite is 1.924 MPa, it can be concluded that the carbon sandwich composite is suitable to be used as a PUNA MALE body material.